Different Levels of Digestible Methionine on Performance of Broiler Starter - Mulyantini, NGA; Ulrikus, RL; Bryden, WL; Li, X (ANIMAL PRODUCTION, 2010)
Dietary protein and amino acid supply is the most expensive component of poultry diets. Therefore several efforts made by the industry to minimize the cost of the protein portion of the diet. Accordingly, there has been a recent move to use digestible amino acid values in the formulation of poultry diets. The efficiency of protein utilization depends to a large extent on the amino acid composition of the diet. The study was conducted to determine the digestible methionine requirement of broilers during the starter periods. One hundred and seventy five (175) chicks were allocated to 5 treatments with five replicates of seven chicks per replicate in a completely randomized design. Chicks were fed experimental diets from one day old to 21 days of age. Dietary treatments included 5 titrated levels each of digestible methionine (3.0, 4.5, 6.0, 7.5, and 9.0 g/kg diet) added to a basal diet. The allowance of digestible methionine, rather than digestible sulphur amino acids was used in formulating the diets.Â  Supplemental synthetic DL-Methionine which were considered to be 100% digestible were added to diets to obtain the concentration of the digestible amino acid. Each week until the conclusion of the trial, birds were individually weighed, feed intake per pen was measured, and feed conversion ratio (FCR) was computed. This study suggested that the digestible methionine requirement for broiler starter is 4.7 g/kg for optimal body weight gain and 4.6 g/kg for optimal feed conversion ratio.Â  (Animal Production 12(1): 6-11 (2010)Key Words: amino acid, broiler, digestible, methionine, starter